A model of quantitative easing at the zero lower bound - Stefan Dürmeier (Bamberg University, Bamberg Economic Research Group (BERG), 2022)
The research question relates to the quantitative impact of government bond purchases of the European Central Bank on inflation and other economic variables at the zero lower bound. At the core is a standard New Keynesian Dynamic Stochastic General Equilibrium model with several financial frictions. The model replicates the intended effect of Quantitative Easing regarding the drop in the government bond yield at the expense of a rise in public debt, and displays the crowding out effect on the balance sheet of the bank which spurs credit and output. Amid lower levels of wages and consumption, the overall quantitative effect is nevertheless not inflationary but deflationary. After a shock to the credit supply, Quantitative Easing is activated more if the zero lower bound on the policy rate is in place. Output after the first period, consumption as well as wages and inflation drop more in the case of the zero lower bound and Quantitative Easing does not make up for the loss. The same findings for the economic performance marked by these four variables are obtained for the analysis at the zero lower bound when a shock hits the exposure of financial intermediaries to public debt.
Keywords: 330; Quantitative Easing; Taylor Rule; Zero Lower Bound; Moral Hazard